2022
DOI: 10.7717/peerj.14128
|View full text |Cite
|
Sign up to set email alerts
|

The impact of children’s temperament on recurrent unintentional injuries: the role of paternal parenting styles as a mediator

Abstract: Background Unintentional injuries (UIs) pose a threat to the health of children all over the world and are a major global health problem. The recurrence of UIs are influenced by the host itself or environmental factors. Children’s temperament and paternal parenting styles (PPS) are important potential factors for poor health outcomes, including recurrent unintentional injuries (recurrent UIs). Therefore, exploring the relationship among these variables may help reduce the likelihood of recurrent UIs in childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…However, in a recent study, none of the three temperament types identified by the Childhood Behaviour Questionnaire have been linked to a higher risk of fracture 9 . Similarly, Zhang et al have also suggested that parenting style could play an important role in mediating children's temperament and recurrent unintentional injury 10 . When these data are evaluated together, it can be thought that not only the temperament of the child but also the factors related to parents might play a role in accidents and injuries.…”
Section: Introductionmentioning
confidence: 98%
“…However, in a recent study, none of the three temperament types identified by the Childhood Behaviour Questionnaire have been linked to a higher risk of fracture 9 . Similarly, Zhang et al have also suggested that parenting style could play an important role in mediating children's temperament and recurrent unintentional injury 10 . When these data are evaluated together, it can be thought that not only the temperament of the child but also the factors related to parents might play a role in accidents and injuries.…”
Section: Introductionmentioning
confidence: 98%